Isolation of a novel mutant gene for soil-surface rooting in rice (Oryza sativa L.) - Hanzawa, Eiko; Sasaki, Kazuhiro; Nagai, Shinsei; Obara, Mitsuhiro; Fukuta, Yoshimichi; Uga, Yusaku; Miyao, Akio; Hirochika, Hirohiko; Higashitani, Atsushi; Maekawa, Masahiko; Sato, Tadashi (Springer, 2013)
Root system architecture is an important trait affecting the uptake of nutrients and water by crops. Shallower root systems preferentially take up nutrients from the topsoil and help avoid unfavorable environments in deeper soil layers. We have found a soil-surface rooting mutant from an M2 population that was regenerated from seed calli of a japonica rice cultivar, Nipponbare. In this study, we examined the genetic and physiological characteristics of this mutant.The primary roots of the mutant showed no gravitropic response from the seedling stage on, whereas the gravitropic response of the shoots was normal. Segregation analyses by using an F2 population derived from a cross between the soil-surface rooting mutant and wild-type Nipponbare indicated that the trait was controlled by a single recessive gene, designated as sor1. Fine mapping by using an F2 population derived from a cross between the mutant and an indica rice cultivar, Kasalath, revealed that sor1 was located within a 136-kb region between the simple sequence repeat markers RM16254 and 2935-6 on the terminal region of the short arm of chromosome 4, where 13 putative open reading frames (ORFs) were found. We sequenced these ORFs and detected a 33-bp deletion in one of them, Os04g0101800. Transgenic plants of the mutant transformed with the genomic fragment carrying the Os04g0101800 sequence from Nipponbare showed normal gravitropic responses and no soil-surface rooting.These results suggest that sor1, a rice mutant causing soil-surface rooting and altered root gravitropic response, is allelic to Os04g0101800, and that a 33-bp deletion in the coding region of this gene causes the mutant phenotypes.